2012
DOI: 10.2478/v10245-011-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Yielding and fruit quality of Lithuanian sweet cherry cultivars grown under the climatic and soil conditions of Warmia

Abstract: In 2006-2008, yielding was determined and biometric measurement as well as chemical analysis was carried out for five Lithuanian sweet cherry cultivars, 'Agila', 'Seda', 'Vasare', 'Ventenue', and 'Jurgita', and two cultivars commonly grown in Poland, 'Ulster' and 'Burlat'. Trees grafted on Mazzard seedlings were planted in 2002 in the orchard of the Pozorty Experimental and Production Institute in the village of Łęgajny near Olsztyn. The highest mean yield for the tested cultivars was obtained in 2008, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
(3 reference statements)
3
12
0
Order By: Relevance
“…Similar conclusion was published by Chełpiński et al (2007) and Erogul (2014), who reported that calcium fertilization did not affect fruit weight. The fruit harvested in our experiment were characterized by slightly greater average weight, width and length than the fruit of the same cultivar studied by Kurlus (2004) and Bieniek et al (2011). Weight, width and length of our fruit were similar to the values reported by Stojanovic et al (2012), who found that average weight of 'Burlat' cv.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar conclusion was published by Chełpiński et al (2007) and Erogul (2014), who reported that calcium fertilization did not affect fruit weight. The fruit harvested in our experiment were characterized by slightly greater average weight, width and length than the fruit of the same cultivar studied by Kurlus (2004) and Bieniek et al (2011). Weight, width and length of our fruit were similar to the values reported by Stojanovic et al (2012), who found that average weight of 'Burlat' cv.…”
Section: Resultssupporting
confidence: 88%
“…According to Sîrbu et al (2012) and Prvulović et al (2011) fruit antioxidant properties depend on many factors, including the species, cultivar, cultivation system, climatic conditions or agrotechnical procedures. L-ascorbic acid concentration in the study fruit seemed to be high, as according to Ferreti et al 2010, Bieniek et al (2011) and McCune et al (2011) its content in sweet cherry is about 7 mg • 100g -1 FW. However, Serrano et al (2005) pointed out that it depended on fruit ripeness, and in ripe fruit its concentration may be as high as 28 mg • 100g -1 FW (Table 2).…”
Section: Resultsmentioning
confidence: 56%
“…Sen et al (2014) observed weight and fruit firmness loss values of three sweet cherry cultivars during the transport and marketing stages. Bieniek et al (2011) found 3.78 g to 6.45 g as mean of three years mean for the weight of sweet cherry fruits for cultivars grown under the climatic and soil conditions of Warmia, Lithuania, while Demirsoy and Demirsoy (2004) reported for local Turkish sweet cherry cultivars values of fruit weight ranging from 2.9 to 7.6 g.…”
Section: Discussionmentioning
confidence: 95%
“…The trees were sprayed with InCa calcium fertilizer based on CaT technology (manufacturer: Plant Impact), containing 8.0% N, 13.0% CaO, and 1.0% Zn [Arysta LifeScience, 2013]. The fertilizer was applied three times, at a dose of 1.5 dm 3 •ha. The first foliar fertilization was performed at the beginning of the flowering period, and the next two took place at fourteen-day intervals.…”
Section: Materials and Research Methodsmentioning
confidence: 99%